Gestão do conhecimento na Pró-Reitoria de Administração da Universidade Federal da Paraíba: proposta de um modelo baseado na norma ISO 30401 - Santos, Débora Henrique Pontes dos (2022)
The present study had the objective to develop a knowledge management model based on ISO 30.401:2018 for Universidade Federal da Paraíba -UFPB Pró-Reitoria. To reach this aim, was necessary to carry out a process of knowing stream survey and identify the elements that facilitate or make difficult the application of the knowl - edge management at Administration Pró-Reitoria – ARP. The theoretical background was substantiated in the concepts, models and practices of knowledge management, emphasizing its application in the Public Higher Educational Institutions. The research is constituted as being qualitative and quantitative, descriptive and exploratory, of applied nature, adopting the techniques of bibliographic and case study research, that had as subjects the administrative technician servants in ARP. For data collection, a virtual questionnaire was applied with questions about the servants’ profile, the cycle of knowledge at AR, and the determinant elements for the knowledge management application. For data analysis were used the knowledge management models and practices mentioned in the research theoretical background, in addition to the requirements and grounds that are on ISO 30.401:2018. Data analysis indicated that the knowledge acquisition, storing and sharing at ARP occurs in an incipient manner, however was shown interest and availability by the employees in participating of a possible knowledge management in ARP, besides having been identified determinant elements for the knowledge management application and its advantages. Based on the obtained results, was possible to develop a Knowledge Management conceptual model, aiming the organizational and personal knowledge organization, besides serving as a guidance tool for managers and servants, in the creation, development and sharing of knowledge.